High-efficiency and low-energy ship recognition strategy based on spiking neural network in SAR images - Xie, Hongtu; Jiang, Xinqiao; Hu, Xiao; Wu, Zhitao; Wang, Guoqian; Xie, Kai (Frontiers in Neurorobotics, 2022)
Ship recognition using the synthetic aperture radar (SAR) images has the important applications in the military and civilian fields. Aiming at the problems of the many model parameters and high energy losses in the traditional deep learning methods for the target recognition in the SAR images, this paper has proposed a high-efficiency and low-energy ship recognition strategy based on the spiking neural network (SNN) in the SAR images. First, the visual attention mechanism is used to extract the visual saliency map from the SAR image, and then the Poisson encoder is used to encode it into a spike train, which can suppress the background noise while retaining the visual saliency feature of the SAR image. Besides, a SNN model integrating the time-series information is constructed by combining the leaked and integrated firing spiking neurons with the convolutional neural network, which can use the firing frequency of the spiking neurons to realize the ship recognition in SAR images. Finally, to solve the problem that SNN model is difficult to train, the arctangent function is used as the surrogate gradient function of the spike emission function during the backpropagation, thus applying this backpropagation method to the training process can optimize the SNN model. The experimental results shows: (1) the proposed strategy can more accurately recognize the ship in the SAR image, and the F1 score can reach 98.55%, which has the better recognition performance than the other traditional deep learning methods; (2) the proposed strategy has the least amount of model parameters (only 3.11MB), which is far less than the model parameters of the other traditional deep learning methods; (3) the proposed strategy has the fewer operations (only 17.97M) and can reach 1/30 time of operands of the other traditional deep learning methods, which shows the high efficiency of the proposed strategy using the spike emission signals; (4) the proposed strategy has the energy loss of 1.38×10−6J, which can achieve the low energy advantage of the nearly three orders of the magnitude compared to the other traditional deep learning methods, indicating that the proposed strategy has a significant energy efficiency.